Memórias da formação inicial e projeções para atuação docente : diálogos sobre avaliação com acadêmicos de educação física - Frossard, Matheus Lima (2015)
This paper aims to understand the debate about teacher training in Physical Education.It was outlined in three chapters that dialogue with each other, considering the nature of the sources studied and the assumed theoretical-methodological assumptions. From the "state of knowledge" type, the first chapter aims to map the academic production on educational evaluation in Physical Education from 1932 to 2014. It reviews 14 journals of the area and finds 56 articles. Based on bibliometric indicators, it establishes four axes of analysis: distribution of articles by year of publication; By newspaper; By authorial origin and author; Distribution by categories and levels of education. The results point to an increase in production over the last four years, compared to the previous decade, although there are still gaps with reference to texts that address pre-primary and secondary education. The second chapter, of a qualitative nature, aims to understand, from autobiographical narrative research, the way in which 45 undergraduate students in Physical Education from seven Brazilian Federal Universities make sense of the evaluative experiences experienced in initial formation. It gives visibility to these evaluative experiences in the student function and in the teaching performance. In a first movement, the students evidence a diversity of evaluation instruments and relate their use to the knowledge taught in each discipline. In the second, they emphasize the need of teacher training courses, besides providing the specific learning of each discipline, should take as central axis the teaching practice. The third chapter is characterized by quantitative and quantitative research. It seeks to analyze how the students in initial formation understand the evaluation processes, considering their teaching performance in stages and / or extracurricular projects. 32 students who responded to work in extracurricular stages and / or projects collaborate with the research. As a source, it uses questionnaires, a focus group and an individual interview. As a result it shows how, what and for what they evaluate in their classes. In this sense, the students evidenced a diversity of evaluative instruments that have helped to materialize the knowledge worked in Physical Education, allowing value judgments and decision making.